Taxes in an efficiency wage economy - Laszlo Goerke (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
Various taxes influence wage and employment outcomes in efficiency wage models. These findings are extended by incorporating more comprehensive tax functions, additional tax parameters, union-firm wage bargaining, and balanced budget restrictions. Moreover, the importance of different effort functions is evaluated. It is shown that higher marginal tax rates, holding constant the level of taxes, reduce wages and increase employment. Higher level of taxes on income, labour cost and value-added can raise unemployment.
Keywords: E24; H24; H25; J41; 330; efficiency wages; effort function; taxes; unemployment; wage bargaining